Analisis Kesejahteraan Masyarakat terhadap Pertumbuhan Ekonomi di Indonesia - Sultan; Heffi Christya Rahayu; Purwiyanta (SAFE-Network, 2023)
Indonesia is one of the main players in the global economy, but if Indonesia's economic growth rate increases, it is not necessarily directly proportional to the level of people's welfare. The welfare of the Indonesian people who are still uneven in terms of the economy and their economic growth which always shows fluctuations every year and even experiences a drastic decline in certain years is the aim of this paper to determine the influence of people's welfare on the development of economic growth in Indonesia. By using the variables Inflation, HDI, Education, poverty, and the unemployment rate as a depiction of social welfare and economic growth which is described using the GDP variable. This analysis was performed using OLS (ordinary least squares)/multiple regression. The OLS uses diagnostic tools, namely the classic assumption test consisting of normality, autocorrelation, multicollinearity and heteroscedasticity. From the results of this analysis, it passes the classical assumption test, which means that the residuals are normal, there are no autocorrelation, heteroscedasticity, and multicollinearity problems. It can be concluded that there is a significant relationship between social welfare and economic growth in Indonesia.